Nomenclature and definition of metabolic-associated fatty liver disease: a consensus from the Middle East and north Africa. (January 2021) - Shiha, Gamal; Alswat, Khalid; Al Khatry, Maryam; Sharara, Ala I; Örmeci, Necati; Waked, Imam; Benazzouz, Mustapha; Al-Ali, Fuad; Hamed, Abd Elkhalek; Hamoudi, Waseem; Attia, Dina; Derbala, Moutaz; et al.
Summary: With the increasing prevalence of obesity and type 2 diabetes, fatty liver disease associated with metabolic dysfunction is a global health problem, especially because it is one of the earliest consequences of obesity and it precedes diabetes development. Fatty liver disease associated with metabolic dysfunction is of particular concern in the Middle East and north Africa, where its prevalence is greater than that in the rest of the world. Despite the magnitude of the problem, no regional guidelines have been developed to address this disease. This Review describes suggestions of redefining fatty liver disease associated with metabolic dysfunction, including its terminology and criteria for diagnosis. Experts have raised serious concerns on the current nomenclature, which labels the disease as non-alcoholic fatty liver disease (NAFLD), and its diagnostic criteria. The panel reached a consensus that the disease should be renamed as metabolic-associated fatty liver disease (MAFLD) and that the disease should be diagnosed by positive criteria. The aim is now to work with authorities across the region to implement these proposed changes and reflect them in health-care policy and to improve health care for patients in this region.